2021
DOI: 10.21037/tau-20-1127
|View full text |Cite
|
Sign up to set email alerts
|

The association between metabolic syndrome and lower urinary tract symptoms suggestive of benign prostatic hyperplasia in aging males: evidence based on propensity score matching

Abstract: Background: To investigate the association between lower urinary tract symptoms suggestive of benign prostate hyperplasia (LUTS/BPH) and metabolic syndrome (MetS) in aging Chinese males. Methods: A dataset that included 3,568 non-MetS cases and 1,020 MetS cases (after data cleansing) was downloaded from the China Health and Retirement Longitudinal Study (CHARLS). To balance the intergroup covariates, propensity score matching (PSM) was employed in the analyses. Univariate logistic regression and multivariate l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 48 publications
4
16
0
Order By: Relevance
“…This association between MetS and LUTS/BPH was in line with previous findings ( 19 22 ). Xiong et al found that men with MetS had 1.47 times of LUTS/BPH than the healthy counterparts in Chinese aging men ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This association between MetS and LUTS/BPH was in line with previous findings ( 19 22 ). Xiong et al found that men with MetS had 1.47 times of LUTS/BPH than the healthy counterparts in Chinese aging men ( 19 ).…”
Section: Discussionsupporting
confidence: 93%
“…This association between MetS and LUTS/BPH was in line with previous findings ( 19 22 ). Xiong et al found that men with MetS had 1.47 times of LUTS/BPH than the healthy counterparts in Chinese aging men ( 19 ). Cosimo et al also disclosed that MetS increased the risk of moderate/severe nocturia in patients with LUTS/BPH ( 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…These include central obesity, insulin resistance and dyslipidemia (Vignozzi et al 2016). In fact, the link between BPH and MetS in humans is well recognized (Ozden et al 2007;Xiong et al 2021). In the current work, MetS was achieved by keeping rats on high-fructose drinking water and high-salt diet.…”
mentioning
confidence: 99%
“…When the standardized deviation of each variable is within ± 10%, it indicates that the matching belongs to the high precision. 33 Finally, subgroup analysis was used to ascertain the consistency of the data from various subgroups. SPSS 25.0 was used for univariate analysis and logistic regression analysis.…”
Section: Methodsmentioning
confidence: 99%